2020
DOI: 10.1111/mpp.12904
|View full text |Cite
|
Sign up to set email alerts
|

Setosphaeria turcica ATR turns off appressorium‐mediated maize infection and triggers melanin‐involved self‐protection in response to genotoxic stress

Abstract: Eukaryotic organisms activate conserved signalling networks to maintain genomic stability in response to DNA genotoxic stresses. However, the coordination of this response pathway in fungal pathogens remains largely unknown. In the present study, we investigated the mechanism by which the northern corn leaf blight pathogen Setosphaeria turcica controls maize infection and activates self‐protection pathways in response to DNA genotoxic insults. Appressorium‐mediated maize infection by S. turcica was blocked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…We have previously shown that the plant fungal pathogen S. turcica has evolved the capacity to breach the intact cuticle of the plant host by elaborating a specialized structure called the appressorium (Gu et al, 2014 ; Zhang et al, 2012 ). Expression of pathogenicity‐related genes is often coupled to appressorium development (Gu et al, 2014 ; Zeng et al, 2020 ; Zhang et al, 2012 ). We therefore performed transcriptome analysis of S. turcica during appressorium development to identify crucial genes that may play essential roles in fungal pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that the plant fungal pathogen S. turcica has evolved the capacity to breach the intact cuticle of the plant host by elaborating a specialized structure called the appressorium (Gu et al, 2014 ; Zhang et al, 2012 ). Expression of pathogenicity‐related genes is often coupled to appressorium development (Gu et al, 2014 ; Zeng et al, 2020 ; Zhang et al, 2012 ). We therefore performed transcriptome analysis of S. turcica during appressorium development to identify crucial genes that may play essential roles in fungal pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…Maize lesions and appressorium development on leaves were observed using a plant infection assay, as described previously, with minor modifications (Ma et al, 2018;Zeng et al, 2020).…”
Section: Appressorium Formation and Plant Infection Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…embl-heidelberg.de/) were used to analyze the conserved domain of the S. turcica xylanase GH11 family genes. And the software IBS (http://ibs.biocuckoo.org/) was used to draw the conserved domain following the procedures described previously [16].…”
Section: Multiple Sequence Alignment Phylogenetic Analysis and Domaimentioning
confidence: 99%